2011
DOI: 10.1055/s-0031-1277154
|View full text |Cite
|
Sign up to set email alerts
|

Bone and Cellular Immune System of Multiparous Sows are Insensitive to Ovariectomy and Nutritive Calcium Shortage

Abstract: of diverse porcine organ systems to their human analogues, the pig ' s usefulness as an osteologic model species is still not entirely clear. However, even though porcine femoral compact bone is predominantly plexiforme, it is converted to well-developed osteonal bone earlier than in sheep [3] . Peak bone mass is obtained with an age of 2 -3 years. The main body of investigations in this area of research was performed using growing minipigs, which, however, might not appropriately refl ect the situation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In the porcine model, RANKL inhibition by rhOPG led to an immediate and significant decrease in serum calcium, phosphorus, and bone turnover markers. Also, µCT analysis of selected bone sites demonstrated an OPG-induced improvement of specific bone architectural indices and bone mineralization [47]. In a similar fashion, cynomolgus macaques responded with significantly depressed bone turnover markers as well as an increase in the bone strength index [48].…”
Section: Novel Antibody-based Therapies Of Osteoporosis and Related Dmentioning
confidence: 99%
See 1 more Smart Citation
“…In the porcine model, RANKL inhibition by rhOPG led to an immediate and significant decrease in serum calcium, phosphorus, and bone turnover markers. Also, µCT analysis of selected bone sites demonstrated an OPG-induced improvement of specific bone architectural indices and bone mineralization [47]. In a similar fashion, cynomolgus macaques responded with significantly depressed bone turnover markers as well as an increase in the bone strength index [48].…”
Section: Novel Antibody-based Therapies Of Osteoporosis and Related Dmentioning
confidence: 99%
“…has received research support and/or honoraria from: Amgen GmbH, Eli Lilly GmbH, Leo Pharma, Merck, Sharp & Dohme GmbH, Nycomed Pharma, Novartis Pharma, Roche Austria, Servier Austria, Institute des Recherches Internationales Servier, Shire, and Sanofi-Aventis. The OPG treatment study of pigs [47] performed by W.S. was financially supported by Amgen, Thousand Oaks, Calif., USA.…”
Section: Disclosure Statementmentioning
confidence: 99%
“…Additionally we tested for alterations in the immune system by means of flow cytometric analyses of PBMC populations and systemic cytokine profiles due to the afore-mentioned importance of the immune system for bone health and disease, which had not been done before in pigs. Unsatisfactorily, we could not induce any osteoporotic phenotype or changes in cellular immunity in these animals [6]. On the other hand, GC treatment in adult minipigs induces significant changes in bone architecture and strength, thus partially resembling osteoporosis in postmenopausal women [7].…”
mentioning
confidence: 72%
“…lated during in vitro osteoclastogenesis and expressed by a variety of diff erent cell types including bone marrow stromal cells and immunocytes in pigs [ 7 ] . Recently, we demonstrated that the skeleton of adult, multiparous sows is unresponsive to diff erent mechanisms of action having severe impact on bone metabolism and structure in other species [ 8 ] . Therefore, we decided to investigate the eff ects of OPG-Fc on bone metabolism markers and bone microstructure of juvenile, growing pigs experiencing much more skeletal plasticity.…”
Section: Affi Liationsmentioning
confidence: 99%